1980
DOI: 10.1159/000459226
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary and Hepatic Activities of Membrane-Bound Enzymes in Man and Rat

Abstract: The lung of adult man contains several times more 5'-nucleotidase (EC 3.1.3.5), alkaline phosphatase (EC 3.1.3.1) and γ-glutamyl-transpeptidase (EC 2.3.2.2) per gram than does that of the 12- to 16-week fetus. In rat lung, too, there is a drastic developmental rise in these activities. Opposite changes in two of the enzymes occur during hepatic differentiation: alkaline phosphatase decreases in the rat, and γ-glutamyl-transpeptidase is ten times higher in the fetal than in the adult liver of both species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
2
0

Year Published

1980
1980
2005
2005

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 4 publications
2
2
0
Order By: Relevance
“…Emphasizing even more strongly the broad validity of the principle of 'fetalism', this principle could be transferable to the human lung. Our results can be interpreted as based on the studies of Knox, [13,14], Greengard and Herzfeld [16] and Bodansky et al [18]. The latter [ 18] regarded that the enzymes AP and GGT in the lung increase drastically their activities with age.…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…Emphasizing even more strongly the broad validity of the principle of 'fetalism', this principle could be transferable to the human lung. Our results can be interpreted as based on the studies of Knox, [13,14], Greengard and Herzfeld [16] and Bodansky et al [18]. The latter [ 18] regarded that the enzymes AP and GGT in the lung increase drastically their activities with age.…”
Section: Resultssupporting
confidence: 71%
“…Our results can be interpreted as based on the studies of Knox, [13,14], Greengard and Herzfeld [16] and Bodansky et al [18]. The latter [ 18] regarded that the enzymes AP and GGT in the lung increase drastically their activities with age. Renal GGT also increases in the course of normal differentia tion of the kidney and after that, Hautman et al [19] demonstrated a decrease in the activ ity of GGT in the urine of patients with renal neoplasms.…”
Section: Resultssupporting
confidence: 71%
“…GGT expression is increased in whole lung after birth [10], but is decreased in adult liver compared to fetal liver [17]. GGT activity is increased in certain liver diseases, after stroke, in tumor tissues, and in other pathologies [18][19][20][21][22][23].…”
mentioning
confidence: 99%
“…The amounts of a chemical constituent, in contrast, can assume any number of values in a continuum. The very advantage of this quantitative method No. 3 ENZYME PATHOLOGY OF LUNG CA Greengard et al 46 1 may be lost if, in the necessary search for contrasts between histologically predefined groups of tumors, one fails to pay due attention to the chemical differences between individual tumors within one such group.…”
mentioning
confidence: 99%